Loss-tolerant stream authentication via configurable integration of one-time signatures and hash-graphs - Goh, A; Poh, GS; Ngo, DCL (2003)
We present a stream authentication framework featuring preemptive one-time signatures and reactive hash-graphs, thereby enabling simultaneous realisation of near-online performance and packet-loss tolerance. Stream authentication is executed on packet aggregations at three levels ie: (1) GM chaining of packets within groups, (2) WL star connectivity of GM authenticator nodes within meta-groups, and (3) signature m-chaining between meta-groups. The proposed framework leverages the most attractive functional attributes of the constituent mechanisms ie: (1) immediate verifiability of one-time signatures and WL star nodes, (2) robust loss-tolerance of WL stars, and (3) efficient loss-tolerance of GM chains; while compensating for various structural characteristics ie: (1) high overhead of one-time signatures and WL stars, and (2) loss-intolerance of the GM chain authenticators. The resultant scheme can be operated in various configurations based on: (1) ratio of GM chain to WL star occurence, (2) frequency of one-time signature affixation, and (3) redundancy and spacing of signature-chain.